A survey of useful wild plants of the Tibetan in Zanda County, Xizang, China - LIN Lei1,2, DING Xiaoyong1, HU Huabin3, ZHANG Dezheng4, WU Guomao1,2, MEI Renqiang1, WANG Yuhua1* (Guangxi Zhiwu)
Wild plants play a pivotal role in people's daily lives, providing numerous necessities such as food, medicine, and living tools for survival. Zanda County, located in the southwestern part of Ngari Prefecture, Xizang Autonomous Region, China, bordering India, serves as an important gateway for China's access to South Asia. This region used to engage in prosperous and lively border trade. The region is characterized by a plateau sub-frigid arid climate, and characterized by low annual average temperature, low oxygen concentration, cold winters, and cool summers. The Tibetan here has amassed rich traditional knowledge on the utilization of wild plants in adapting to the harsh environment. To comprehensively and systematically investigate, document, and study the traditional knowledge of the Tibetan in Zanda County on the utilization of wild plants, ethnobotanical investigation methods were adopted. The research involved interviews with 173 informants, recording 3 639 utilization reports(URs), and conducted quantitative analyses using use value(UV), cultural value(CV), and cultural importance index(CII)metrics. The results are as follows:(1)The Tibetan in Zanda County possesses extensive traditional knowledge on the utilization of wild plants, employing 119 species, belonging to 40 families and 83 genera.(2)The utilization categories of wild plants in this area are diverse, with eight utilization categories, and multiple plants possessing two or more uses simultaneously.(3)The most significant plants in people's lives are Carum carvi(UV=1.220), Artemisia stracheyi(UV=0.919), Rheum acuminatum(UV=0.890), Cupressus sp.(UV=0.769), and Urtica dioica(UV=0.757). Theses plants are intimately connected to the lives of the local Tibetan and are deeply loved by them.(4)The intricate and diverse plateau environment significantly influences the utilization of wild plants in this region. This study not only comprehensively and systematically documents the utilization knowledge and characteristics of wild plants in Zanda County, but also contributes to the further exploration and rational utilization of local plant resources, and promotes the inheritance of traditional knowledge, contributing to the prosperity of local culture. In addition, this study has positive implications for biodiversity conservation, helping to raise public awareness and protection consciousness towards biodiversity, and promoting the balance and harmonious development of the ecosystem.